The Instruments for Measuring Patient-Centred Care in Clinical Care Settings: a Systematic Literature Review - Siswanto, Heri; Asmaningrum, Nurfika; Rondhianto, Rondhianto (Universitas Malahayati, 2024)
ABSTRACT Patient-centred care has different dimensions, necessitating a clear definition to facilitate consistent measurement and evaluation of patient-centred care in clinical settings. This systematic literature review aims to identify and compare measuring tools related to patient-centred care in clinical settings. The Prisma framework was employed to explore six databases (i.e., Google Scholar, PubMed, Science Direct, Springer, MDPI, and Sage Journal) for literature review in identifying instruments used to measure patient-centred care in clinical settings. Result Of 13 articles included in this review, 13 articles documented different questionnaires measuring patient-centred care. These questionnaires included The Person-centred Primary Care Measure (PCPCM), Person-centred maternity care (PCMC), Chloe's-Card, Korean version of the Person-centred Care Assessment Tool (K-P-CAT), Health Education Impact Questionnaire (HEI-Q), Patient-centred Matching (PCPM), Quality of Interactions Schedule (QuIS), Person-centred Critical Nursing Care Scale, Patient-centred Quality of Cancer Care Questionnaire (PCQCCQ), Patient-reported Experience Measures (PREMs), Patient-centred Survivorship Care Index (PC-SCI), and Vietnamese Patient-centred Care measure (VPCC). Each instrument had different criteria according to the patient's background and contextual setting. Existing questionnaires have engaged various perspectives in measuring patient-centred care and distinct adjustment to the patient's condition. Some of the reviewed instruments were modified from existing instruments to meet particular settings. Keywords: Measuring, Patient-Centred Care, Clinical Care, Instruments